The Roles of Group Status and Group Membership in the Practice of Hypodescent. Issue 3 (8th July 2019) - Roberts, Steven O.; Ho, Arnold K.; Gülgöz, Selin; Berka, Jacqueline; Gelman, Susan A.
Abstract : Hypodescent emerged in U.S. history to reinforce racial hierarchy. Research suggests that among contemporary U.S. adults, hypodescent continues to shape social perception. Among U.S. children, however, hypodescent is less likely to be endorsed. Here, we tested for hypodescent by introducing U.S. children (ages 4–9) and adults ( N  = 273) to hierarchically ordered novel groups (one was high status and another was low status) and then to a child who had one parent from each group. In Study 1, we presented the groups in a third‐party context. In Study 2, we randomly assigned participants to the high‐status or the low‐status group. Across both studies, participants did not reliably endorse hypodescent, raising questions as to what elicits this practice.